Challenges in Medicine: The Odyssey of a Patient with Isolated IgG4-Related Eosinophilic Angiocentric Fibrosis Presenting as a Locally Destructive Sinonasal Mass - Snigdha Nutalapati; Richard O’Neal; William O’Connor; Brett T. Comer; Gerhard C. Hildebrandt (Case Reports in Rheumatology)
Eosinophilic angiocentric fibrosis (EAF) is an exceeding rare clinical entity and is considered a part of the spectrum of IgG4-related disease (IgG4RD). We hereby present such an unusual case of a 60-year-old female who presented to us with recurrent sinonasal mass, after a decade long haul of multiple clinical evaluations, biopsies, and debulking surgery without a definitive diagnosis. Over this period, the mass eroded through the ethmoid cells along with nasal septal destruction leading to saddle nose deformity, extended superiorly through the cribriform plates to right frontal lobe, and compressed the optic nerve leading to visual loss. Although initial biopsy was negative, repeat biopsy was performed owing to high clinical suspicion due to all the classic histopathological findings compatible with the diagnosis of eosinophilic angiocentric fibrosis IgG4-related disease (EAF-IgG4RD). Steroids are the recommended first-line therapy; however, our case was resistant to steroids needing rituximab to halt the disease progression. Our case interestingly also had T-cell clonality and isolated isocitrate dehydrogenase 2 enzyme mutation on next-generation sequencing, suggesting a possible role of novel molecular-targeted therapies in this rare disease. This case highlights the clinical challenges physicians face towards diagnosing and treating EAF-IgG4RD, emphasizing the need for high clinical suspicion and the possible role of targeted therapies for this rare disease.